Antibacterial therapy of acute biliary tract infections (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
this article is devoted to antibacterial therapy of acute biliary tract infections.